Role of Dietary Fiber in Chronic Disease Prevention: A Comprehensive Review - Phadnis, Meenal (AG Volumes, 2025)
Dietary fibre is vital to human health and may be found in plant-based meals. It comes in two varieties, soluble and insoluble, both of which have important health advantages. The purpose of this article is to review the diverse literature that has been conducted on the function of dietary fibre in the prevention of chronic diseases. This review emphasises the critical role that dietary fibre plays in avoiding chronic conditions such obesity, type II diabetes, cardiovascular disease, and inflammation. Better insulin sensitivity, weight control, and general metabolic health are all facilitated by both insoluble and soluble fibres. Improving assessment tools and establishing a harmonised global definition are indispensable for the advancement of public health policies and research. The promotion of fiber-rich diets through the consumption of fruits, vegetables, whole cereals, and legumes, as well as the provision of affordable nutritious foods and education, is essential. In order to improve long-term results and lower illness burdens across a variety of groups, healthcare practitioners should include fibre recommendations into the treatment of chronic diseases.